ASIMILASI ANTARA KETURUNAN ARAB DENGAN ORANG MELAYU DI KELURAHAN TANJUNG KECAMATAN MUNTOK - Andi Saputra (MEDIOVA: Journal of Islamic Media Studies, 2021)
This study analyzes the assimilation that occurs between the Arab descendants and the Malays in Tanjung Sub-District, Muntok District, West Bangka. The method of this study was a descriptive qualitative method. The results of this study portray that the assimilation between Arab descendants and the Malays in Tanjung Sub-District has occurred since a long time ago. This assimilation does not suddenly occur, but there are several driving and inhibiting factors of this occurrence. The driving factors include religious similarity, trade (equal opportunity in the economic field), and mutual respect. On the contrary, the inhibiting factors consist of poor communication, lack of understanding of the other culture, as well as lack of sympathy for the other group. In addition, there are seven forms of assimilation that occur in Tanjung Sub-District, which are marital assimilation (amalgamation), cultural assimilation, structural assimilation, identification assimilation, attitude reception assimilation, behavior reception assimilation, and civic assimilation.